Mechanical Fracture of Aluminium Alloy (AA 2024-T4), Used in the Manufacture of a Bioproducts Plant (2023)
Aluminium alloy (AA2024-T4) is a material commonly used in the aerospace industry, where it forms part of the fuselage of aircraft and spacecraft thanks to its good machinability and strength/weight ratio. These characteristics allowed it to be applied in the construction of the structure of a pilot plant to produce biological extracts and nano-encapsulated bioproducts for the phytosanitary control of diseases associated with microorganisms in crops of Theobroma cacao L. (Cacao). The mechanical design of the bolted support joints for this structure implies knowing the performance under fatigue conditions of the AA2024-T4 material since the use of bolts entails the placement of circular stress concentrators in the AA2024-T4 sheet. The geometric correction constant (Y) is a dimensionless numerical scalar used to correct the stress intensity factor (SIF) at the crack tip during propagation. This factor allows the stress concentration to be modified as a function of the specimen dimensions. In this work, four compact tension specimens were modeled in AA2024-T4, and each one was modified by introducing a second circular stress concentrator varying its size between 15 mm, 20 mm, 25 mm, and 30 mm, respectively. Applying a cyclic load of 1000N, a load ratio R=-1 and a computational model with tetrahedral elements, it was determined that the highest SIF corresponds to the specimen with a 30 mm concentrator with a value close to 460 MPa.mm0.5. Where the crack propagation had a maximum length of 53 mm. Using these simulation data, it was possible to process each one and obtain a mathematical model that calculates the geometric correction constant (Y). The calculated data using the new model was shown to have a direct relationship with the behavior obtained from the simulation.